2018
DOI: 10.1002/jcp.27832
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib plus endocrine therapy in HER2 negative, hormonal receptor‐positive, advanced breast cancer: A real‐world experience

Abstract: Data from 423 human epidermal growth factor receptor 2‐negative (HER2−), hormone receptor‐positive (HR+) advanced breast cancer (aBC) patients treated with palbociclib and endocrine therapy (ET) were provided by 35 Italian cancer centers and analyzed for treatment outcomes. Overall, 158 patients were treated in first line and 265 in second/later lines. We observed 19 complete responses and 112 partial responses. The overall response rate (ORR) was 31% (95% confidence interval [CI], 26.6–35.4) and clinical bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…With a longer follow-up, subsequent large US and international studies have shown similar PFS data and have suggested an OS benefit [13,14]. Other, more limited studies, were in line with those results [26][27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 58%
“…With a longer follow-up, subsequent large US and international studies have shown similar PFS data and have suggested an OS benefit [13,14]. Other, more limited studies, were in line with those results [26][27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 58%
“…Additional studies36,37 are summarized in Table 2 and are consistent with the data previously reported in activity and safety. Interestingly, Pizzuti and colleagues reported a reduced ORR in patients with prior exposure to everolimus/exemestane (16.7 versus 34.5%, respectively, p =0.002) and a higher ORR and CBR in patients without visceral metastasis ( p =0.0004 and 0.04, no data available).…”
Section: Real-life Studiessupporting
confidence: 83%
“…On the other hand, no statistically significant difference in ORR was observed according to previous fulvestrant exposure (31.7 versus 29.6%, p =0.72) and menopausal status. The study also supports the use of palbociclib in an elderly population (≥75 years) with no differences in the toxicity profile depending on treatment line and patients’ age 37…”
Section: Real-life Studiessupporting
confidence: 72%
“…The safety profile was analyzed for metastatic patients and for non-metastatic patients. Overall, 19 trials including 3378 patients were analyzed for the metastatic group, and 5 trials including 792 patients for the non-metastatic group [18,19,22,[26][27][28][29][30][31][32][33][34][35][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Trials with abemaciclib were excluded from analysis, because no trials were available in a non-metastatic setting [54][55][56][57][58].…”
Section: Safety Results In Metastatic and In Non-metastatic Patientsmentioning
confidence: 99%